Yarn eveness control in 1 mm range - Monteiro, Sérgio (2000)
In order to be able to quantify yarn evenness, testing instruments were developed, based on different methods and progressively improving their performance . Most of them use principle based on drawing the yarn under test between the plates of a condenser, so that the yarn and the air are the dielectric material that changes the capacitor characteristics, which is proportional to the mass of small lengths of the yarn (8 mm). Knowledge of the yarn mass in 1mm range is of most importance to evaluated properly the yarn evenness; furthermore several irregularities can only be properly detected of this mass evaluation is possible in this range. In this paper, a study is presented in order to achieve mass variation in 1mm length. Simulation results are presented and compared with Uster Tester III.